Proteomic analysis of the European flounder Platichthys flesus response to experimental PAH–PCB contamination. Issue 2 (30th June 2015) - Galland, Claire; Dupuy, Célie; Loizeau, Véronique; Danion, Morgane; Auffret, Michel; Quiniou, Louis; Laroche, Jean; Pichereau, Vianney
Graphical abstract: Highlights: The proteome modifications of Platichthys flesus liver in response to a mixture of PAH/PCB were studied. 34 proteins were significantly deregulated, of which 18 were identified by using Maldi TOF–TOF mass spectrometry. Oxidative stress- and glutathione metabolism-(GST, GPx) proteins were deregulated. Proteins from the methionine cycle (BHMT, SHMT, SAHH) were deregulated. Abstract: Platichthys flesus is often used as a sentinel species to monitor the estuarine water quality. In this study, we carried out an experimental contamination of fish using a PAHs/PCBs mixture, which was designed to mimic the concentrations found in the Seine estuary (C1) and 10 times these concentrations (C2). We used a proteomic approach to understand the molecular mechanisms implied in the response of P. flesus to these xenobiotics. We showed that 54 proteins were differentially accumulated in one or several conditions, which 34 displayed accumulation factors higher than two. 18 of these proteins were identified by MALDI TOF–TOF mass spectrometry. The results indicated the deregulation of oxidative stress- and glutathione metabolism-(GST, GPx) proteins as well as of several proteins belonging to the betaine demethylation pathway and the methionine cycle (BHMT, SHMT, SAHH), suggesting a role for these different pathways in the P. flesus response to chemical contamination.